Efektivitas Komposisi Media Tanam dan Durasi Perendaman terhadap Viabilitas dan Pertumbuhan Bibit Sengon (Falcataria moluccana): Effectiveness of Growing Media Composition and Soaking Duration on Viability and Seedling Growth of Sengon (Falcataria moluccana) - Hasanah, Nurul (Jurnal Kehutanan dan Lingkungan, 2025)
This study aimed to evaluate the effect of growing media composition and seed soaking duration on the germination and growth of sengon seedlings. The research was conducted using a factorial experiment arranged in a Randomized Block Design (RBD). The first factor was growing media composition consisting of three volume ratios: topsoil+compost (3:1), topsoil+sand (3:1), and topsoil+compost+sand (3:1:1). The second factor was seed soaking duration: 12 hours, 24 hours, and 36 hours. The results showed that there was no interaction between growing media and soaking duration treatments on all observed parameters. Independently, the topsoil+compost (3:1) media showed the best performance on germination rate and stem diameter growth up to 12 Weeks After Planting (WAP). Meanwhile, soaking seeds for 12 hours proved to be the most efficient in stimulating germination rate, whereas soaking for 36 hours tended to increase stem diameter at later stages. Based on these results, the use of a topsoil and compost mixture along with a 12-hour seed soaking duration is recommended for effective and efficient sengon nursery practices.